Discovery of 4-aminopyrimidine analogs as highly potent dual P70S6K/Akt inhibitors. (15th October 2021) - Xiao, Yufang; Huck, Bayard R.; Lan, Ruoxi; DeSelm, Lizbeth; Chen, Xiaoling; Qiu, Hui; Neagu, Constantin; Johnson, Theresa; Mochalkin, Igor; Gardberg, Anna; Jiang, Xuliang; Tian, Hui; et al.
Graphical abstract: Abstract: Activation of the PI3K/Akt/mTOR kinase pathway is associated with human cancers. A dual p70S6K/Akt inhibitor is sufficient to inhibit strong tumor growth and to block negative impact of the compensatory Akt feedback loop activation. A scaffold docking strategy based on an existing quinazoline carboxamide series identified 4-aminopyrimidine analog 6, which showed a single-digit nanomolar and a micromolar potencies in p70S6K and Akt enzymatic assays. SAR optimization improved Akt enzymatic and p70S6K cellular potencies, reduced hERG liability, and ultimately discovered the promising candidate 37, which exhibited with a single digit nanomolar value in both p70S6K and Akt biochemical assays, and hERG activities (IC50  = 17.4 μM). This agent demonstrated dose-dependent efficacy in inhibiting mice breast cancer tumor growth and covered more than 90% pS6 inhibition up to 24 h at a dose of 200 mg/kg po.